Hybrid – Flexible (HyFlex) Learning Preparedness of Pre-Service Teachers in A Private College - Navarro, Lerma (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the preparedness of pre-service teachers in implementing HyFlex learning in terms of pedagogical, technological, assessment, and classroom management knowledge and skills, affective or psychological readiness, and the ability to address challenges in flexible learning environments. Anchored on the Community of Inquiry (CoI) Framework, the Technological, Pedagogical, and Content Knowledge (TPACK) Framework, and Self-Efficacy Theory, the study employed a quantitative correlational research design. The respondents consisted of third- and fourth-year pre-service teachers enrolled in field study subjects at Saint Louis College. Total enumeration was utilized, and data were gathered through a researcher-developed 5-point Likert scale questionnaire administered online through Google Forms and QR codes. Frequency counts, percentages, mean ratings, and Pearson-r moment correlation were used to analyze the data. The findings revealed that pre-service teachers were generally Very Prepared to Very Highly Prepared in HyFlex learning. Technological knowledge and classroom management obtained the highest preparedness ratings, while assessment knowledge obtained the lowest among the measured domains. Respondents also demonstrated Very Highly Prepared affective and psychological readiness and were Very Prepared in addressing HyFlex learning challenges. The study further revealed very strong positive and statistically significant relationships among HyFlex knowledge and skills, affective or psychological readiness, and preparedness in addressing HyFlex learning challenges, with the strongest relationship found between knowledge and skills and addressing challenges in HyFlex learning. Based on the findings, a validated HyFlex Sustainability Program (HSP) was developed to strengthen pre-service teachers’ competencies in flexible learning environments. The study concluded that pre-service teachers possess high levels of preparedness for HyFlex learning due to their familiarity with digital technologies, access to internet connectivity and devices, and exposure to virtual learning platforms. The study recommends integrating the HyFlex Sustainability Program into teacher education curricula, strengthening technological and assessment training, and investing in HyFlex learning infrastructure and professional development initiatives. The study supports Sustainable Development Goal (SDG) 4 on Quality Education by promoting inclusive, equitable, and flexible learning opportunities. It also aligns with SDG 9 on Industry, Innovation, and Infrastructure and SDG 10 on Reduced Inequalities through the integration of digital technologies and accessible learning modalities. The study contributes to educational and institutional sustainability by strengthening teacher preparedness, promoting digital resilience, and supporting the continuity of quality education during disruptions and emergencies.